Characterization Studies, Photophysical and Aggregation Emission Properties of New Fluorescent 5-(4-(1H-phenanthro[9,10-d]imidazole-2-yl)phenyl)-2,4-dichlorophenyl-1,3,4-thiadiazole-2-amine - Zurnacı, Merve; ŞENER, İzzet; GÜR, Mahmut; ŞENER, Nesrin (ASOS Yayinevi, 2023)
Phenanthroimidazole derivative compounds attract attention in optoelectronic device technology, especially in OLEDs, thanks to their chemical, thermal, photophysical and photochemical properties. For this reason, phenanthroimidazole derivatives are most promising compounds for these application in the future. In this study, -diCl bearing phenanthroimidazole compound was synthesized, characterized and investigated the photophysical and aggregation properties in detail. Spectroscopic studies for its characterization were used 1H-NMR, ATR-IR and detailed LCMS-MS (mass and product ion scan). The absorption and emission spectra of diCl-PHN have been recorded with solvents of different polarities at room temperature. diCl-PHN was exhibit high fluorescence quantum yield in DMSO with 0.78. CIE chromaticity diagram results of diCl-PHN were obtained and display good intensity. Additionally, aggregation properties were recorded at seven different water concentrations (water/DMSO %). With the results obtained as a result of the study, it was concluded that this phenanthroimidazole derivative compound is a suitable molecule for fluorescent applications.